The sintering kinetics of shellfish porcelain reinforced by sepiolite nanofibres. Issue 10 (17th October 2018) - Tian, Li; Wang, Lijuan; Wang, Kailei; Zhang, Yuedan; Liang, Jinsheng; Zhang, Yi
Abstract : The work investigated the effect of sepiolite nanofibres on mechanical properties and sintering behaviour of shellfish porcelain. Samples of shellfish porcelain reinforced by sepiolite nanofibres were fired in an electric furnace at 1150, 1200 and 1250°C for a period of 80, 100, 120 and 140 min. Sintered samples were characterized by flexural strength, fracture toughness, scanning electron microscopy, transmission electron microscopy and X-ray diffraction. The results showed that 2 wt% sepiolite nanofibres could increase the flexural strength and fracture toughness of the porcelain bodies through the fibre pullout and the weak interface mechanisms. Sintering activation energies were determined according to the linear shrinkage results. It is found that the liquid-phase sintering mechanism of shellfish porcelain with sepiolite nanofibres is a diffusion mechanism. Porcelain without sepiolite is controlled by volume diffusion, and eventually, the grain boundary diffusion began to appear with the increase of sepiolite addition.